Hyperandrogenic Origins of Polycystic Ovary Syndrome – Implications for Pathophysiology and Therapy - Abbott, David H (Expert Rev Endocrinol Metab, 2019)
INTRODUCTION: Polycystic ovary syndrome (PCOS) diagnosis comprises combinations of female hyperandrogenism, menstrual irregularity and polycystic ovaries. While it is a familial and highly prevalent endocrine disorder, progress towards a cure is hindered by absence of a definitive pathogenic mechanism and lack of an animal model of naturally occurring PCOS. AREAS COVERED: These include an overview of PCOS and its potential etiology, and an examination of insights gained into its pathogenic origins. Animal models derived from experimentally-induced hyperandrogenism during gestation, or from naturally-occurring PCOS-like traits, most reliably demonstrate reproductive, neuroendocrine and metabolic pathogenesis. EXPERT COMMENTARY: Genetic studies, while identifying at least 17 PCOS risk genes, account for <10% of women with PCOS. A number of PCOS risk genes involve regulation of gonadotropin secretion or action, suggesting a reproductive neuroendocrine basis for PCOS pathogenesis. Consistent with this notion, a number of animal models employing fetal androgen excess demonstrate epigenetic induction of PCOS-like traits, including reproductive neuroendocrine and metabolic dysfunction. Monkey models are most comprehensive, while mouse models provide molecular insight, including identifying the androgen receptor, particularly in neurons, as mediating androgen-induced PCOS-like programming. Naturally-occurring female hyperandrogenism is also demonstrated in monkeys. Animal models are poised to delineate molecular gateways to PCOS pathogenesis.